The Role of Parents in Accompanying Children's Learning Activities at Home - Putri, Besti Nora Dwi; Suryadi, Suryadi (Holistic Science, 2024)
This qualitative study aims to understand the multifaceted roles of parents in assisting children's learning at home, prompted by the observation that some parents lack involvement or neglect their children's academic performance. Employing a descriptive qualitative approach, this research involved two parents as key informants and four children as additional informants. Data were collected through interviews and observations to gain in-depth insights into parental roles. The findings reveal that parents play diverse roles in supporting children's learning, acting as teachers at home who guide and help children understand learning materials, facilitators who provide learning resources like school supplies, motivators who offer encouragement and support, and influencers or directors who guide the development of children's talents and interests. Although some parents face challenges in maintaining consistent involvement or fully understanding their children's talents and interests, this study emphasizes the importance of active parental involvement in supporting children's learning at home as educators, resource providers, motivators, and mentors to optimally develop children's potential.